Factors contributing to road traffic accidents in suburban areas - E. V. Pechatnova; I. A. Novikov; I. I. Kiryushin; N. N. Nagorny (Вестник СибАДИ)
Introduction. Accidents in cities and outside populated areas have their own characteristics, which have been studied in various works. However, changes in the characteristics of traffic, pedestrian flows, and those of the street and road environment structure usually are not observed on crossing the city boundaries. Calculations show that it is in the suburban zone that the highest accident density is estimated, as well as a high proportion of accident-hazardous areas. Besides, there has been an increase in the suburbanization process, which leads to the growth of suburban areas. In this regard, assessing the impact of various factors on accidents within the suburban boundaries is an urgent research task.   The aim of the study is to investigate the influence of environmental factors on accidents in suburban areas (the city of Barnaul is observed as an example).   Materials and methods. In this study the suburban zone of Barnaul was considered as an example, the boundaries of the zone being defined according to the transport methodology. The empirical basis of the work was data on accidents that were recorded for the sections of federal highways within the boundaries of the suburban zone in the period from 2018 to 2023. For each accident from the sample, the period of day and weather conditions (air temperature, precipitation rate and wind speed) were determined. The relative risk theory was used to assess the influence of the factors selected.   Conclusions. The study identified the distinctive features of accidents in suburban areas in comparison with those of suburban and urban road conditions. The influence of the group of key external factors was also assessed: periods of the day and weather conditions. Among the former, day, civil, navigational, astronomical twilight and night periods were distinguished. As for the latter, air temperature, precipitation rate and wind speed were analyzed.   Limitations of the study/implications for future research. The results of the study can be used in further comprehensive research of accidents in suburban areas of large cities.   Practical implications. The identified features of accidents and the dependence of the relative risk of accidents in the suburban area on external factors can be used for preventive measures development, as well as in the development of intelligent transport systems.   Originality. For the first time, the dependences of the relative risk of accidents in the suburban area as a result of a group of key environmental factors (period of the day and weather conditions) were determined.